Revitalisasi Ajaran al-Qur’an untuk Memperkuat Ketahanan Keluarga dan Masyarakat di Era Digital: (Studi atas Q.S. At-Tahrim [66]:6) - Lintang Dewi Fi'liya Putri; Aanisah Mucholifah (Lembaga Penelitian, Penerbitan, dan Pengabdian Masyarakat (LP3M) Institut Agama Islam Bakti Negara (IBN) Tegal, 2026)
The development of digital technology has transformed patterns of social life, family values, and the religious dynamics of Muslim societies. This advancement offers significant opportunities for the dissemination of knowledge and da‘wah, yet it also poses challenges in the form of moral disorientation, weakened family communication, and increasing digital individualism. This study aims to examine the relevance of Qur’anic teachings in building family and societal resilience in the digital era, with a particular focus on Q.S. At-Tahrim [66]:6 as its normative foundation. Employing a thematic (maudhu‘i) tafsir approach, this research explores the core values contained in the verse related to spiritual, moral, and social responsibilities within the family context. The findings indicate that the Qur’an provides a resilience framework grounded in the values of taqwa, amanah, and ukhuwah, which can be contextually implemented through family education, Islamic digital literacy, and the strengthening of social ethics in cyberspace. The revitalization of Qur’anic teachings thus becomes a strategic step in reinforcing family integrity while fostering a harmonious and resilient society in the face of value disruption in the digital age. This study contributes to the development of contemporary Islamic studies, particularly in the fields of family resilience and Qur’an-based social ethics.